Stabilized photorefractive running holograms, with arbitrarily selected phase shift, for material characterization - de Oliveira, Ivan; Freschi, Agnaldo A.; Fier, Igor [UNESP]; Frejlich, Jaime (Optical Soc Amer, 2012)
We report on the recording of stabilized running holograms in photorefractive materials with arbitrarily selected phase shift phi between the transmitted and difracted beams propagating along the same direction behind the photorefractive crystal. The dependence of the diffraction efficiency and of the hologram speed on phi, in such stabilized holograms, can be easily measured and used for material characterization. In this communication we applied for the first time this technique for studying and characterizing hole-electron competition in a nominally undoped titanosillenite crystal sample. (C) 2012 Optical Society of America